Evaluation of a Radiographic Method to Detect Tibial Dyschondroplasia Lesions in Broilers - Pelicia, Ky; Aparecido Jr, I. M.; Garcia, E. A. [UNESP]; Molino, A. B. [UNESP]; Santos, G. C. [UNESP]; Berto, D. A. [UNESP]; Vieira Filho, J. A. [UNESP]; Murakami, E. S. M. [UNESP]; Montenegro, A. T. [UNESP]; Silva, A. M. (Facta-fundacio Arnco Ciencia Tecnologia Avicolas, 2012)
This study aimed at developing radiographic techniques for the early detection of dyschondroplastic lesions in the tibia of broilers. The experiment was carried out at the facilities of UNIFOR/MG and Formiga and UNIFENAS/Alfenas with 420 one-day-old male Cobb broilers. At 20 days of age, all birds were radiographed and identified with an alpha-numeric metal ring in the right leg. At 40 days of age, 42 broilers previously selected as a function of bone mineral density and lesion thickness scores were again radiographed and scored, and then sacrificed. Their right tibia was removed for gross and histological examination of the growth plate. The results showed that radiographic techniques are correlated with gross and histological examination and that there was no significant differences among techniques (P>0.05). it was concluded that the use of radiographic examination to identify tibial dyschondroplasia in broilers precludes the use of bone mineral density to diagnose this condition. The non-parametric statistical Chi-square test at 5% significance level was used to analyze the results.
Keywords: Broiler production; histology; gross examination; radio-diagnosis; tibia